METHODOLOGICAL COMPETENCE AS THE FOUNDATION FOR FUNDAMENTALIZING THE PROFESSIONAL TRAINING OF FUTURE ECONOMICS TEACHERS - Djumanazarova Zamira Kojabayevna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2026)
This paper examines methodological competence as a key foundation for the fundamentalization of professional training of future economics teachers. In the context of rapid socio-economic transformations, digitalization, and increasing demands for the quality of economic education, the role of teachers’ methodological preparedness becomes critically important. The study conceptualizes methodological competence as an integrative component of professional competence that combines pedagogical knowledge, research skills, analytical thinking, and the ability to apply modern teaching methods in economics education. The research is based on a systematic analysis of pedagogical theories, competency-based and activity-based approaches, as well as comparative analysis of contemporary models of teacher training. The paper substantiates that the fundamentalization of professional training should not be limited to subject knowledge alone, but must be grounded in the development of methodological thinking, reflective skills, and the ability to design and evaluate educational processes. The results indicate that a high level of methodological competence enables future economics teachers to effectively integrate theoretical knowledge with practical application, adapt to innovative educational technologies, and foster students’ economic thinking and problem-solving skills. The study highlights methodological competence as a strategic factor in improving the quality and sustainability of economics teacher education and provides recommendations for enhancing teacher training programs in higher education institutions.